Wireless: Some Facts and Figures from a Corpus-driven Study - Rea Rizzo, Camino (International Journal of English Studies, 2009)
Wireless is the word selected to illustrate a model of analysis designed to determine the specialized character of a lexical unit. Wireless belongs to the repertoire of specialized vocabulary automatically extracted from a corpus of telecommunication engineering English (TEC). This paper describes the procedure followed in the analysis which is intended to fulfil a twofold purpose: first, to validate the automatic classification; and second, to gain a better insight on the lexical profile of telecommunication English. The statistical information provided by the variables of frequency, distribution and keyness, are combined with the data extracted from the exploration of the surrounding co-text, in order to describe the sintagmatic relations established.